2012
DOI: 10.1186/1556-276x-7-202
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional heterostructure of metallic nanoparticles and carbon nanotubes as potential nanofiller

Abstract: The effect of the dimensionality of metallic nanoparticle-and carbon nanotube-based fillers on the mechanical properties of an acrylonitrile butadiene styrene (ABS) polymer matrix was examined. ABS composite films, reinforced with low dimensional metallic nanoparticles (MNPs, 0-D) and carbon nanotubes (CNTs, 1-D) as nanofillers, were fabricated by a combination of wet phase inversion and hot pressing. The tensile strength and elongation of the ABS composite were increased by 39% and 6%, respectively, by adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Conductive llers provide conductive ability for ECA, so the performance of llers can greatly affect the conductive performance of the composites. The conductive llers of ECA are mainly include metal powders, graphite, carbon nanotubes [8][9][10][11][12][13][14]. The metal ller has good conductivity and usually include silver, copper, gold, chromium, nickel and lead-free alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Conductive llers provide conductive ability for ECA, so the performance of llers can greatly affect the conductive performance of the composites. The conductive llers of ECA are mainly include metal powders, graphite, carbon nanotubes [8][9][10][11][12][13][14]. The metal ller has good conductivity and usually include silver, copper, gold, chromium, nickel and lead-free alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is urgent to develop a simple, easier-to-operate, safe, and controllable method to prepare nest-like nanofiber structures with a higher binding force to the titanium substrate under room temperature and normal pressure. With the development of nanotechnology in recent years, it has been shown that nanoscale morphology can significantly expand a specific surface area ( Kim et al, 2012 ; Shin et al, 2016 ; Li et al, 2017 ; Ourari et al, 2019 ) to increase the chemical reaction rate ( Hou et al, 2018 ; Hamans et al, 2020 ; Zhang et al, 2020 ). Shin et al reported that 70-nm titanium nanoparticles can be etched in a KOH solution to prepare a titanium nest-like structure at room temperature, which is based on the mechanism of those nanoparticles that have a higher specific surface area ( Shin et al, 2016 ) and increase the effective contact area of KOH and TiO 2 and reduce the reaction temperature.…”
Section: Introductionmentioning
confidence: 99%